ROLE OF MUSIC THERAPY IN ANESTHESIA - Pareek Ashish; Singh Narinder; Verma Kalpana (International Journal of Applied Ayurved Research, 2017)
Patients referred for surgery experience varying degrees of perioperative anxiety and fear. Anxiety is accompanying with increases in heart rate and blood pressure and other alterations that can have a undesirable impact preoperatively; during the induction, maintenance, and emergence periods of anesthesia; and postoperatively. The anesthesiologist efforts to de-crease the extent of the problem by administering tranquilizers, of which benzodiazepines are the most effective. But those drugs have adverse properties, such as excitement, hyperactiv-ity, and prolonged amnesia. Music therapy is a non-pharmacological intervention that has the ability to decrease anxiety levels in some patients. There are ample indications that relaxing music is effective in regulation of nervousness and activation of the autonomous nervous system triggered by preoperative anxiety. Based on this, the implantation of preoperative mu-sic therapy by anesthesiologists is advisable.